The man who died seven times - Nishizawa, Yasuhiko, 1960 December 25- (Pushkin Vertigo, Pushkin Press, 2025)
"In the middle of the family New Year's gathering at his home, Grandfather Fuchigami is murdered. But not for the last time. For his grandson, Hisataro, has fallen into a mysterious time-loop, in which he must relive the same day again and again. Every morning after his grandfather's death, Hisataro wakes up with a chance to find the culprit and prevent the murder. But day after day he fails, despite stumbling across clues aplenty in the shape of secret plots, illicit love affairs and jealous rivalries. With an extremely large inheritance up for grabs, everyone is a suspect -- and Hisataro is beginning to wish he could leave this day behind..."--